Variation of milk urea nitrogen according to milk yield and milk protein in Holstein cows in Boyacá, Colombia - Tarazona-Manrique, Luis Edgar (2023)
The aim of this study was to determine the variation of milk urea nitrogen (MUN) concentration according to milk yield and milk protein in Holstein cows in Boyacá, Colombia. Data previously collected (n=4901) over two years were used. Univariate analysis of variance was performed with the variables milk yield (l/day) and milk protein (%) as independent variables and the concentration of MUN as the dependent variable. In addition, a simple linear correlation analysis was performed between each variable. The results showed that MUN values are higher when milk yield is lower, but no statistical differences were found for MUN concentration according to milk protein content. Weak and negative correlation was found between milk yield and MUN concentration, but no significant correlation was found between milk protein and MUN concentration.